(untitled) (Social Science Review, 2025)
The indigenous Munda community living in the Sundarbans of Bangladesh for generations is now at severe risk of losing their language and culture due to excessive integration with the Bengali-speaking people. Moreover, this landless community, which has survived through oppression and was deprived of basic rights, lagged in getting a proper education. Though a certain number of government and NGO initiatives have been taken and some projects are still in force to lift this disaster-stricken community. They are largely centred on climate change risk reduction and livelihood context. Very little has been done to ensure the preservation of their language and culture and, more importantly, to provide education. This article aims to present a brief historical outline of their language, education, and culture, and to explore how changes in these aspects are reflected in the real-life experiences of the Mundas living near the Sundarbans. Besides, it looks at how the ‘longing’ for cultural homogeneity provokes the dominant community to exploit the Mundas, who, with no other way, are unlikely to be driven to keep on collaborating. Social Science Review, Vol. 42(1), June 2025, pp. 209-227